Promoting religious acceptance: the relationship between intercultural competence and religious attitudes among Third Culture Kids - Melles, Elizabeth A. (Mental health, religion & culture, 2017)
The study explored whether intercultural competence was a significant predictor of religious attitudes among Third Culture Kids (TCKs), individuals who had spent their developmental years abroad. It also examined whether growing up as a missionary kid (MK) would predict religious attitudes. Two hundred and seventy-six TCKs from 37 countries and 19 religious affiliations completed the web-based survey that included measures of intercultural competence, religious attitudes and beliefs, and demographic information. Intercultural competence was a significant predictor of participants’ desire for all religions to be treated fairly whereas growing up as an MK was a significant predictor of participants’ desire for their religion to be unchallenged and of less desire for interreligious dialogue. The findings suggest that increasing intercultural competence may be a way to promote religious acceptance.